Properties of sustainable concrete with substitution of quarry dust as recycled fine aggregate - Wan Mohd Hakimie Wan Mohd Nasir (Penerbit Universiti Malaysia Perlis, 2011)
Concrete is the most widely used manmade product in the world. But the depletion of the natural fine aggregate and the requirement for reduction in the cost of concrete production has resulted in the increased need to identify alternative of fine aggregate used in concretes. Quarry dust, a by-product from the crushing process during quarrying activities in the studied material. This study investigates some characteristic of quarry dust and discusses the potential of quarry dust to be used as substitution for sand in concrete. The properties of quarry dust that were determined are particle size distribution and specific gravity. Besides that, slump for 20%, 60% and 100% of substitution for concrete mix design based on BS 5328 tested in order to determine the wright w/c ratio. Then, the 7, 14 and 28 days compressive strength of those concrete specimens, were tested. This test purposely for comparison between standard mixes with substitution concrete mix. Results obtained shows that standard mix possesses higher compressive strength. But the optimum substitution is at 60% due to the results almost same with standard mix. All test cubes results are acceptable according concrete grade 20 which mean all specimens should have compressive strength higher than 20MPa.